2017
DOI: 10.1007/s11356-017-8937-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategic tillage in conservation agricultural systems of north-eastern Australia: why, where, when and how?

Abstract: Farmers often resort to an occasional tillage (strategic tillage (ST)) operation to combat constraints of no-tillage (NT) farming systems. There are conflicting reports regarding impacts of ST and a lack of knowledge around when, where and how ST is implemented to maximise its benefits without impacting negatively on soil and environment. We established 14 experiments during 2012-2015 on farms with long-term history of continuous NT to (i) quantify the associated risks and benefits to crop productivity, soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…The use of strategic tillage, which is the practice of occasionally cultivating NT soils, can help with weed, pest and disease management, nutrient stratification, and compaction in continuous long-term NT systems (Kirkegaard et al, 2014;Dang et al, 2015Dang et al, , 2018. However, in order to successfully identify practices appropriate for different geographical regions and cropping systems, adequate research is required to develop effective and locally adapted approaches.…”
Section: Agronomic Challengesmentioning
confidence: 99%
“…The use of strategic tillage, which is the practice of occasionally cultivating NT soils, can help with weed, pest and disease management, nutrient stratification, and compaction in continuous long-term NT systems (Kirkegaard et al, 2014;Dang et al, 2015Dang et al, , 2018. However, in order to successfully identify practices appropriate for different geographical regions and cropping systems, adequate research is required to develop effective and locally adapted approaches.…”
Section: Agronomic Challengesmentioning
confidence: 99%
“…A priori, farm managers might think that a conservation tillage system can be hard to maintain for a long period of time because weeds can take hold in these systems, and be difficult to control (Sullivan, Young, Smiley, & Alldredge, 2013). Dang et al (2018) posed that the use of a one-time strategic tillage during a sustained period of CA could help with weed control. It was observed that weed populations were more controlled with one-time strategic tillage than NT, but results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with climate change increasingly evident in the unpredictability of rainfall, it seems clear that minimum tillage can be the best option for Salsola control. Dang et al (2018) concluded that disc tillage is effective for weed management during the fallow period. In NT systems, if herbicide use is to be reduced, other techniques need to be implemented and minimum tillage techniques (i.e.…”
Section: Source Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques commonly used for remediation and management of soil compaction in that region are chiselling and subsoiling to depths between 280 and 450 mm, and to less extent controlled traffic farming and axle load reduction, respectively [7]. Yield responses to chiselling and subsoiling are generally satisfactory, but growers' evidence suggests that the beneficial effects of deep tillage are transient, also noted in related studies [8]. The objectives of this work were to: (a) quantify changes in soil physical properties of an Entic haplustoll as induced by deep tillage (subsoiler and chisel plow) operations conducted over two growing seasons, (b) improve growers' awareness of potential negative effects of field traffic on loose soil following deep tillage operations, (c) determine the effect of deep tillage on sunflower yield, and (d) quantify fuel and draft required to conduct deep tillage operations on this soil.…”
Section: Introductionmentioning
confidence: 91%